1956
DOI: 10.1139/y56-046
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors Affecting the Level of Plasma Cholesterol in Humans: The Role of Fat

Abstract: Three dietary experiments have been performed in which 36, 37, and 49 male medical students and staff members participated as experimental subjects. In each study, everyone consumed the same homogeneous formula diet for eight days at which time they were divided into five groups. One group was maintained on the original diet for a further eight days and the others were given diets varying in respect of the level and nature of the fat moiety. Protein supplied 16.9% of total calories in all experimental rations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1957
1957
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…About the same time, it was shown that the addition of polyunsaturated fat to a fat-free diet resulted in a reduction in plasma cholesterol levels, which was of the same magnitude as the rise observed when saturated fats were added. 37 The possibility that hypercholesterolemia resulted from EFA deficiency was discounted when it was shown that a fish oil high in co-3 polyunsaturates but low in linoleic acid effectively reduced plasma cholesterol levels.…”
Section: Plasma Cholesterolmentioning
confidence: 99%
“…About the same time, it was shown that the addition of polyunsaturated fat to a fat-free diet resulted in a reduction in plasma cholesterol levels, which was of the same magnitude as the rise observed when saturated fats were added. 37 The possibility that hypercholesterolemia resulted from EFA deficiency was discounted when it was shown that a fish oil high in co-3 polyunsaturates but low in linoleic acid effectively reduced plasma cholesterol levels.…”
Section: Plasma Cholesterolmentioning
confidence: 99%
“…It has long been recognized that the substitution of polyunsaturated fat for saturated triglycerides in the diet results in a reduction in plasma cholesterol levels (1)(2)(3)(4). Although the mechanism(s) responsible for this effect remains poorly understood, the relationship between various dietary lipids and plasma cholesterol levels in man has been studied in considerable detail (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor is the fatty acid composition of the dietary fat. The substitution of polyunsaturated fat for saturated fat in the human diet generally has led to a lowering of serum cholesterol levels (13)(14)(15)(16)(17)(18). Most investigators who have altered dietary fat composition by substituting polyunsaturated for saturated fat have used either cholesterol-free formula diets or diets with reduced cholesterol content.…”
mentioning
confidence: 99%